Efektivitas Penggunaan Media Loose Parts dalam Meningkatkan Kemampuan Literasi Numerasi Anak Usia Dini Se - Kecamatan Cipedes Kota Tasikmalaya - Mardia, Rahma (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
Loose parts media, which are simple and flexible materials such as wood, stone, rope, and other natural objects, can contribute to the development of early childhood numeracy literacy. Loose parts media can help children develop math skills through various manipulative activities that involve critical thinking and problem solving. Children can build, count, compare, order, and classify loose parts objects in a variety of contexts, such as in construction, nature exploration, and art. The use of loose parts media can also help children develop language and literacy skills. When children use loose parts to build a story, they will learn about narrative structure, speaking and listening skills, and writing skills. The research method used is descriptive qualitative method. In developing early childhood numeracy literacy, the use of loose parts media can be a very effective and fun tool to help children build skills and understanding of mathematics and language actively and creatively. The conclusion in this study is that loose parts media has a very large effect on the development of early childhood numeracy literacy in Cipedes District, Tasikmalaya City